Effects of linear versus curvilinear sprint training on multidirectional speed in young soccer players: a randomized parallel-group trial - Solleiro-Duran, David; Cidre-Fuentes, Pablo; Rey, Ezequiel; Baena-Raya, Andrés; Filter, Alberto; Padrón-Cabo, Alexis (Biology of Sport, 2025)
The purpose of this study was to examine the effects of linear sprint training (LST) compared to curvilinear sprint training (CST) using an equivalent session training volume, on linear (LS) and curvilinear (CS) sprint performance, horizontal force-velocity profile, and change of direction (COD) ability in young soccer players. In a randomized pre-post parallel-group trial design, nineteen U16 male soccer players were randomly assigned to LST ( n = 9) and CST ( n = 10) groups. Both groups performed 11 sprint training sessions over 6 weeks. Before and after the training period, LS (5 m, 10 m, 15 m, 20 m, and 30 m), CS (weak and good side), horizontal force-velocity profile, and COD speed (modified 505 test) were assessed. The LST showed small to moderate significant enhancements ( p ≤ 0.05) in LS (except 5 m sprint), modified 505 test, theoretical maximal velocity (V 0 ), maximal power output (P max ), and maximal ratio of force (RF peak ) from pre‑test to post‑test. CST resulted in small to moderate significant improvements ( p ≤ 0.05) in 10 m, 20 m, and 30 m LS performance, weak and good sides of the CS, COD speed, and P max from pre‑test to post‑test. In addition, significant between-group comparisons were observed between LST and CST for CS performance in both sides ( p < 0.01). In conclusion, LST and CST seem to produce trajectory-specific adaptations in young soccer players. Therefore, strength and conditioning coaches should integrate both LST and CST training methods to effectively prepare soccer players and enhance their sprinting performance.